The influence of fluid structure interaction modelling on the dynamic response of ships subject to collision and grounding. (January 2021) - Kim, Sang Jin; Kõrgersaar, Mihkel; Ahmadi, Nima; Taimuri, Ghalib; Kujala, Pentti; Hirdaris, Spyros
Abstract: Analysis of the dynamic response of ships in accident scenarios requires a realistic idealisation of environmental and operational conditions by multi-physics models. This paper presents a procedure that simulates the influence of strongly coupled FSI effects on the dynamic response of ships involved in typical collision and grounding events. Our method couples an explicit 6-DoF structural dynamic finite element scheme with a hydrodynamic method accounting for (a) 6-DoF potential flow hydrodynamic actions; (b) the influence of evasive ship speed in the way of contact and (c) the effects of hydrodynamic resistance based on a RANS CFD model. Multi-physics simulations for typical accident scenarios involving passenger ships confirm that suitable FSI modelling may be critical for either collision or grounding events primarily because of the influence of hydrodynamic restoring forces. Highlights: We present an FSI model for assessing ship crashworthiness. Our model simulates ship evasiveness, seakeeping and hydrodynamic resistance. An explicit FEA scheme is used to couple structural dynamics and hydrodynamics. FSI simulations confirm the influence of hydrodynamic restoring forces on dynamic response.